1993
DOI: 10.1111/j.1471-4159.1993.tb03572.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Melatonin Production by Pineal Photoreceptor Cells: Role of Cyclic Nucleotides in the Trout (Oncorhynchus mykiss)

Abstract: The light/dark cycle influences the rhythmic production of melatonin by the trout pineal organ through a modulation of the serotonin N-acetyltransferase (NAT) activity. In static organ culture, cyclic AMP (cAMP) levels (in darkness) and NAT activity (in darkness or light) were stimulated in the presence of forskolin, isobutylmethylxanthine, or theophylline. Analogues of cAMP, but not of cyclic GMP, induced an increase in NAT activity. Light, applied after dark adaptation, inhibited NAT activity. This inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 26 publications
3
33
0
2
Order By: Relevance
“…A similar situation may exist with control versus FSK-treated 1E7 cells. Data on the pike pineal gland in culture are also in agreement with this hypothesis, because it has been found the DBcAMP treatment increases melatonin production Ͼ10-fold, without markedly increasing AANAT activity measured in broken cell preparations (15).…”
Section: Fig 1 Aanat In Cos7 and 1e7 Cells Detected By Intact Cell supporting
confidence: 74%
See 1 more Smart Citation
“…A similar situation may exist with control versus FSK-treated 1E7 cells. Data on the pike pineal gland in culture are also in agreement with this hypothesis, because it has been found the DBcAMP treatment increases melatonin production Ͼ10-fold, without markedly increasing AANAT activity measured in broken cell preparations (15).…”
Section: Fig 1 Aanat In Cos7 and 1e7 Cells Detected By Intact Cell supporting
confidence: 74%
“…Although most data are consistent with the view that AANAT activity is regulated by controlling the steady-state levels of AANAT protein, limited observations in the literature point to the existence of another regulatory mechanism through which melatonin production might change without altering AANAT protein and AANAT activity as estimated in broken cell preparations (13)(14)(15). This hypothetical activation/ inactivation mechanism is of special interest, because it may explain the very rapid physiological increase in circulating melatonin seen at the onset of the dark period in humans as well as other species (1, 16 -18).…”
mentioning
confidence: 53%
“…in addition to these molecular adaptations some cellular mechanisms are probably involved, which transduce the temperature effect and regulate melatonin secretion. One target might be the cyclic AMP-dependent pathway (Thibault et al, 1993). Previous studies have shown that the dark induced rise in cyclic AMP induces AANAT phosphorylation through the RRNH and RRNS sequences at both ends of the molecule (present in the two AANAT2 Arctic charr isoforms); this allows binding of the enzyme to a chaperone protein (14-3-3), providing higher stability and preventing degradation through the proteasome (Falcón et (saAANAT2_IA, light blue; saAANAT2_VV, blue; AANAT2_VA mutant, green; omAANAT2_IV, purple).…”
Section: Discussionmentioning
confidence: 99%
“…Only salmonids, including rainbow trout, are an exception to this rule. In all salmonid species investigated to date it has been demonstrated that pineal melatonin synthesis does not involve an endogenous clock, so that lack of melatonin oscillation has been described under constant conditions (Thibault et al, 1993;Gern and Greenhouse, 1988;Mizusawa et al, 2000;Migaud et al, 2007). However even under constant darkness several core circadian genes continue to cycle in other trout neural regions (retina and hypothalamus) (López-Patiño et al, 2011a) that are involved in the regulation of daily rhythms of several parameters such as feeding behavior and locomotor activity (Cuenca and de la Higuera, 1994;Sánchez-Vázquez and Tabata, 1998).…”
Section: Introductionmentioning
confidence: 99%